2005
DOI: 10.1111/j.1471-0528.2005.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of different treatment strategies with intrapartum antibiotic prophylaxis to prevent early‐onset group B streptococcal disease

Abstract: Objective To estimate the costs and effects of different treatment strategies with intrapartum antibiotic prophylaxis to prevent early-onset group B streptococcal (GBS) disease in the Netherlands. The treatment strategies include a risk-based strategy, a screening-based strategy, a combined screening/risk-based strategy and the current Dutch guideline. Design Cost-effectiveness analysis based on decision model. Setting Obstetric care system in the Netherlands.Population/Sample Hypothetical cohort of 200,000 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 18 publications
1
21
0
1
Order By: Relevance
“…Further studies using real-time PCR performed in intrapartum setting were needed to identify targeted population and settings where the test will be most useful. In these last years, studies not supporting the intrapartum PCR screening as a cost-effective strategy in comparison with culture screening at around 35-37 weeks of gestation, used data from older less accurate PCR equipment [32,113].…”
Section: Non-culture Methods For Intrapartum Specimen Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies using real-time PCR performed in intrapartum setting were needed to identify targeted population and settings where the test will be most useful. In these last years, studies not supporting the intrapartum PCR screening as a cost-effective strategy in comparison with culture screening at around 35-37 weeks of gestation, used data from older less accurate PCR equipment [32,113].…”
Section: Non-culture Methods For Intrapartum Specimen Processingmentioning
confidence: 99%
“…The use of risk-based policy in these nations reflect the belief that their low national incidence of GBS EOD will likely not decrease further with the introduction of universal culture-based screening, and solely increase maternal-fetal exposure to the adverse effects of antibiotics, mainly antimicrobial resistance and potential anaphylactic reactions [30,31]. For these countries, the implementation of universal GBS screening may lead as well to further medicalization of labor and require more counseling and a higher level of care for many more women, increasing costs and increasing the risk of obstetrical interventions [29,32].…”
Section: Current Prevention Strategies Used In European Countries Andmentioning
confidence: 99%
“…Articles were excluded for the following reasons: analysis of a combination of interventions without the possibility to single out the impact of an antibiotic (six articles) or analysis of an intervention that did not include an antibiotic (five articles). The analysis included 23 articles that reported information about 85 incremental cost-utility ratios of antibiotics [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]. The characteristics of included cost-utility analyses are described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Trijbels et al reported that the incidence of neonatal GBS disease fell hardly at all after the introduction of the guideline and recommended a change to the national guideline. In 2005, Van den Akker et al compared the cost-effectiveness of the Dutch guideline with the risk-based strategy, the screening strategy and the combination strategy in a theoretical model [20]. This analysis took into account the unique maternity care system in the Netherlands, which involves a 31% home birth rate and a stratified care model with different professional care providers at different risk levels.…”
Section: Introductionmentioning
confidence: 99%